PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA BUDHA SISWA KELAS IV SDN 003 TEMBILAHAN KOTA - Ratno Ratno (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is motivated by the low learning result of Buddha's education of fourth grade students, from 20students 10 people who scores above KKM, This research is a classroom action research conducted on fourthgrade students of SDN 003 Tembilahan Kota. The subject of this research is the fourth grader of SDN 003Tembilahan Kota, this research is carried out in two cycles, each cycle is done by stages: planning,implementation, observation, and reflection. Based on the research results obtained data that the learning resultof religious education Budah students have increased, in cycle I the number of students who reach KKM is 15students (75%) in cycle II the number of students who reach KKM amounted to 17 people (85%).